Multipoint left ventricular pacing effects on hemodynamic parameters and functional status: HUMVEE single-arm clinical trial. (14th October 2021) - Konstantinou, K; Xydis, P; Antoniou, C K; Magkas, N; Manolakou, P; Chrysohoou, C; Dilaveris, P; Gatzoulis, K; Tsioufis, K
Abstract: Objectives: The aim of this study was to assess the capacity of optimized multipoint pacing (MPP) over optimized cardiac resynchronization therapy (CRT), in terms of clinical, functional, and echocardiographic parameters among dyssynchronous heart failure patients. Methods: Eighty patients (Caucasian, 77.5% male, 68.4±10.1 years, 53.8% ischemic cardiomyopathy) sequentially received optimized CRT and optimized MPP over 6 and 12-month periods, in a single-arm clinical trial. Clinical, laboratory and echocardiographic assessment was conducted at baseline and following completion of each step. Results: Significant additive effects of optimized MPP over optimized CRT were noted regarding 6-minute walking distance (baseline/optCRT/optMPP: 293±120m vs 367±94m vs 405±129m, p<0.001), NYHA class (2.36 vs 2.19 vs 1.45, p<0.001), VTIlvot (14.25±3.2cm vs 16.2±4cm vs 17.5±3.4cm, p<0.001), stroke volume (48±13.5ml vs 55±15ml vs 59±15ml, p<0.001), LVEF (29%±7.1% vs 33%±7.3% vs 37%±7.7%, p<0.001), maximal left atrial volume (77.2±34.2ml vs 74.2±39.5ml vs 67.7±32ml, p=0.02), pulmonary artery systolic pressure (35.9mmHg vs 33.5mmHg vs 31mmHg, p<0.001), and right ventricular strain (−8.3%±6.9% vs −8.8%±6.6% vs −11.8%±6.1%, p=0.022). Regarding VAC SW and CP as percentages of maximal, there was significant difference detected compared to baseline for both CRT and MPP. Additive effects persisted only if suitable MPP dipoles were present. Exploratory analysis revealed that ischemic cardiomyopathy continued to exhibit significant differences favoring MPP, whereas nonischemic cardiomyopathy had similar findings regarding total left atrial strain and quality of life. Conclusions: Optimized MPP showed significant improvements on hemodynamic parameters and ventricular function, in heart failure patients over optimized CRT. The beneficial effect was more prominent in men and in those with rather reduced LVEF, consistent with findings suggesting a beneficial trend in VAC and CP with the more homogenous depolarization offered by optimized MPP Funding Acknowledgement: Type of funding sources: None.